OPTIMALISASI LITERASI FISIK: BAGAIMANA KARAKTERISTIK BUKU CERITA BERGAMBAR YANG MENARIK UNTUK ANAK SEKOLAH DASAR (Jurnal Pedagogik Olahraga, 2025)
Picture storybooks have great potential in supporting the physical literacy of elementary school-aged children with a combination of narrative, visual, and movement experience elements. This study aims to analyze the characteristics of interesting picture storybooks and can be maximized as part of actualizing physical literacy in elementary school children. This research approach uses a systematic literature review method with PRISMA guidelines with the stages of identification, screening, eligibility, and inclusion of articles. The inclusion criteria are determined as follows: articles published in the last five years (2019-2024), using a qualitative, quantitative, or R&D approach, and discussing the development or application of picture storybooks in the context of children's education. A total of 140 identified articles were then processed into six articles that met the criteria and further analyzed thematically. The findings of the study with three main themes, namely: (1) narrative elements that encourage active involvement of children, (2) visualization with characters that can strengthen focus and understanding of movement, and (3) an embodied cognition approach in integrating physical activity into stories. A synthesis of the study results suggests that effective picture books not only present narratives and visualizations, but also foster children's interest in reading, understanding, and motivation to be more active. Therefore, picture books are a strategic medium for developing physical literacy in elementary schools.
Keywords: karakteristik, buku, literasi fisik, sekolah dasar.